FILM ANIME DRAGON BALL SEBAGAI MEDIA DIPLOMASI BUDAYA JEPANG DRAGON BALL ANIME FILM AS A MEDIUM OF JAPANESE CULTURAL DIPLOMACY - Ramadana Alien Jaya; Setyasih Harini; GPH Dipokusumo (Solidaritas: Jurnal Ilmu-Ilmu Sosial, 2020)
This research analyzes and explains how the influence of anime films on Japanese cultural diplomacy. As for the background of this writing because the anime film is one of Japan's popular culture that is easily accepted by the world community and is experiencing growth in this modern era. Japan is a country that routinely conducts cultural diplomacy. Japan believes that a cultural approach can build good relations between Japan and other countries. Japanese cultural diplomacy tends to use popular culture such as anime, manga, music, or fashion. This research focuses on the Dragon Ball anime film because this anime is one of the successful anime films abroad and the main character was chosen as one of the mascots of the 2020 Tokyo Olympics. Based on this, this study aims to find out how the Dragon Ball anime film influences as a diplomatic media Japanese culture. This research was examined using the theory of cultural diplomacy. This research method uses descriptive qualitative research methods with secondary data collection. From the research conducted, the researchers found that the Dragon Ball anime film as a medium of cultural diplomacy had a positive impact on enhancing Japan's positive image and foreign relations. The success of this cultural diplomacy can be seen from the high sales of anime-themed products and the increasing number of foreign tourists visiting Japan. Keyword : Anime, Pop Culture, Cultural Diplomacy